Hakikat Berpikir Dalam Perspektif Psikologi Islam - Hafizallah, Yandi; Zayadi, Zayadi; Zamzami, Nurshafa Ainun (Tawshiyah: Jurnal Sosial Keagaman dan Pendidikan Islam, 2024)
This article aims to discuss the nature of thinking in the perspective of Islamic psychology. Islamic psychology is an integral concept of the practice dimension and the scientific dimension, this practice-scientific dimension that fully binds humans into spiritual behavior patterns. The paradigm of Islamic Psychology shows that human 'reality' is bound through epistemological, ontological, and axiological aspects. This is in line with what is found in the Qur'an with the terms dabbara (contemplate), Faqiha (understand), tafakkara (think), Tadzakara (remember) and Fahima (understand). The Qur'an also describes various terminologies such as tadhakkur, which is a derivation from the root word dhakara meaning to remember, the term al-tafakkur comes from the word fakara meaning power or power that leads to knowledge, the term ta'aqqul in terms of language has several meanings, lexically the word ta'aqqul comes from the word 'Aqa which has the meaning of thinking while taddabur thinks of the meaning behind the explicit meaning, also called thinking about what is implied behind the explicit.